Perancangan Mebel Fleksibel pada May May Salon Tunjungan Plaza Surabaya - Yusuf, Michelle Cleodora (Intra, 2017)
Tunjungan Plaza is one of the largest and most famous malls in Surabaya and even in Southeast Asia, this mall is demanded by the people of Surabaya due to the completeness of products and services offered, The salon is one of the examples of services at Tunjungan Plaza Mall that is highly demanded by the public due to it’s popularity and quality. For example, May May Salon that I used as the site of my design project, the most popular activity in this salon is haircut and nail art, but the amount of facilities for both activities are not the same, so that it can’t improve the services of this salon, therefore it needs a flexible furniture that can comply needs in one furniture, it can also be used as a new innovation.